Peningkatan Nilai Tambah Limbah Kayu melalui Program Kemitraan Masyarakat (PKM) di Desa Serenan Kecamatan Juwiring Kabupaten Klaten - Sulistyono, Bambang; Santoso, Arief Iman; Widiyanti, Emi (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2019)
The production process of wood crafts for interior furniture leaves a lot of wood waste, where the remnants of wood pieces are pieces of wood that have a high selling price and if processed with a touch of art will be unique products with high economic value. Serenan Village is a village of furniture and carving centers that are rich in potential resources to produce products of high artistic value and economy. Seeing this potential, several efforts were made to empower the furniture and carving businessmen there in the form of several activities, among others, improving the quality and production capacity through the introduction of planer machines, improving the quality and variety of wood profiles by introducing router machines, processing wood waste into ashtrays carved and cigar places, skills improvement with design training, production and finishing processes and market expansion with the construction of a marketing website and participation in product exhibitions. With the Community Partnership Program activity, it can increase motivation for partners to continue to improve product competitiveness and continue to utilize existing waste into high-value products.